Asociación entre geohelmintiasis y signos clínicos en niños de edad escolar - Valderrama Pomé, Aldo Alim (2024)
The aim of this study was to determine the association between soil-transmitted helminth infections and clinical signs in school-age children. The study was basic level, analytical in design, observational and cross-sectional. It included a sample size of 471 school-age children in 2017, through simple random sampling, who were asked for a faecal sample and a history was taken to identify clinical signs. Faecal eggs were identified using rapid sedimentation (RST) and Kato-Katz techniques. The t test was applied to determine the difference between means and the Pearson Chi-square test and Odds ratio to establish associations at a 95% reliability level and α=0.05 for the confidence intervals. The overall prevalence of soil-transmitted helminth infections was 52.5% (259/493; 95%CI=48.0-57.1). The prevalence of Ascaris lumbricoides was 51.1%, Trichuris trichiura 1.8% and Ancylostoma sp 0.6%. The prevalence of ascariasis in women was higher than that in men (p˂0.05). Hookworm infection was associated with age (p˂0.01), weight (p˂0.01) and height (p˂0.01) of the schoolchildren. A. lumbricoides reached a severe parasite load. The schoolchildren mainly presented fever, nausea, vomiting, diarrhoea, pain, paleness and flatulence. Ascariasis was associated with constipation (OR=1.7; p˂0.016) and epigastric pain (OR=1.6; p˂0.01).